A Review of Water‐Resistant Hemicellulose‐Based Materials: Processing and Applications. Issue 2 (28th December 2016) - Farhat, Wissam; Venditti, Richard A.; Hubbe, Martin; Taha, Mohamed; Becquart, Frederic; Ayoub, Ali
Abstract: Hemicelluloses, due to their hydrophilic nature, may tend to be overlooked as a component in water‐resistant product applications. However, their domains of use can be greatly expanded by chemical derivatization. Research in which hydrophobic derivatives of hemicelluloses or combinations of hemicelluloses with hydrophobic materials are used with to prepare films and composites is considered herein. Isolation methods that have been used to separate hemicellulose from biomass are also reviewed. Finally, the most useful pathways to change the hydrophilic character of hemicelluloses to hydrophobic are reviewed. In this way, the water resistance can be increased and applications of targeted water‐resistant hemicellulose developed. Several applications of these materials are discussed. Abstract : Like water off a duck's back ! Hemicelluloses, owing to their hydrophilic nature, may be overlooked as a component in water‐resistant product applications. However, their domains of use can be greatly expanded by chemical derivatization. The most useful pathways to change the hydrophilic character of hemicelluloses are reviewed. Several applications of these materials are discussed.